SAS text analytics for business applications : concept rules for information extraction models - Jade, Teresa; Wilsey, Biljana Belamaric; Wallis, Michael (SAS Institute, 2019)
Extract actionable insights from text and unstructured data. Information extraction is the task of automatically extracting structured information from unstructured or semi-structured text. SAS® Text Analytics for Business Applications: Concept Rules for Information Extraction Models focuses on this key element of natural language processing (NLP) and provides real-world guidance on the effective application of text analytics. Using scenarios and data based on business cases across many different domains and industries, the book includes many helpful tips and best practices from SAS text analy.